Carotid endarterectomy with primary closure versus patch angioplasty in patients with symptomatic and significant stenosis: protocol for a systematic review with meta-analyses and trial sequential analysis of randomised clinical trials - Marsman, Martijn S (BMJ Open, 2019)
INTRODUCTION: Use of patch angioplasty in carotid endarterectomy (CEA) is suggested to reduce the risk of restenosis and recurrent ipsilateral stroke. The objective is to conduct a systematic review with meta-analysis and trial sequential analysis as well as Grading of Recommendations Assessment, Development and Evaluation (GRADE) assessments comparing the benefits and harms of CEA with primary closure of the arterial wall versus CEA with patch angioplasty in patients with a symptomatic and significant carotid stenosis. METHODS AND ANALYSIS: The review shall be conducted according to this published protocol following the recommendations of the ‘Cochrane’ and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Randomised clinical trials comparing CEA with primary closure of the arterial wall versus CEA with patch angioplasty (regardless of used patch materials) in human adults with a symptomatic and significant carotid stenosis will be included. Primary outcomes are all-cause mortality at maximal follow-up, health-related quality of life and serious adverse events. Secondary outcomes are symptomatic or asymptomatic arterial occlusion or restenosis, and non-serious adverse events. We will primarily base our conclusions on meta-analyses of trials with overall low risk of bias. However, if pooled point estimates of all trials are similar to pooled point estimates of trials with overall low risk of bias and there is lack of a statistical significant interaction between estimates from trials with overall high risk of bias and trials with overall low risk of bias we will consider the precision achieved in all trials as the result of our meta-analyses. ETHICS AND DISSEMINATION: The proposed systematic review will collect and analyse secondary data from published studies therefor ethical approval is not required. The results of the systematic review will be disseminated by publication in a peer-review journal and submitted for presentation at relevant conferences. PROSPERO REGISTRATION NUMBER: CRD42014013416.